2016
DOI: 10.1210/jc.2016-1025
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in Androgens and Estrogens Are Associated With All-Cause and Cause-Specific Mortality in Older Men

Abstract: Dynamic temporal changes in serum T, cFT, DHT, and E2 (but not E1, LH, FSH, and SHBG) in older men are associated with all-cause and cause-specific mortality in distinct patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 44 publications
7
57
2
Order By: Relevance
“…Conversely, no relationship between sex steroids and cognition was found in other studies, such as the MMAS, 136 the CHAMP, 137 and the MrOS. 97 In these large cohort studies, low serum free T was almost constantly associated with an increased all-causes mortality risk, this association was found by the HIMS, 138 CHAMP, 81 MMAS, 139 EMAS, 95 RBS, 119 Tromsø, 140 and MrOS 141 studies. In the MrOS the mortality risk appeared to be higher when also low serum E 2 was present.…”
Section: Main Outcomes Of Cohort Studiesmentioning
confidence: 77%
See 1 more Smart Citation
“…Conversely, no relationship between sex steroids and cognition was found in other studies, such as the MMAS, 136 the CHAMP, 137 and the MrOS. 97 In these large cohort studies, low serum free T was almost constantly associated with an increased all-causes mortality risk, this association was found by the HIMS, 138 CHAMP, 81 MMAS, 139 EMAS, 95 RBS, 119 Tromsø, 140 and MrOS 141 studies. In the MrOS the mortality risk appeared to be higher when also low serum E 2 was present.…”
Section: Main Outcomes Of Cohort Studiesmentioning
confidence: 77%
“…The BLSA estimated a decline of total serum T around 3.2 ng/dl per year, 4,79 this esteem being around 1.9 pg/ml per year in the RBS, 80 while the first data coming from the MMAS reported a decline of serum total and free T of about 0.4% and 1.2% per year, respectively 53 (Table 3). More recently, the CHAMP study showed a decline of serum total T around 2% per year 81 ( Table 3). The EMAS results have confirmed, in the last years, the data concerning the progressive decline in aging men of serum total T, free T, and E 2 82 , as well as those concerning the rise of SHBG with aging 83 (Table 3).…”
Section: Risk Increasementioning
confidence: 98%
“…Current knowledge on the relation between endogenous oestradiol and cardiovascular risk in men is limited and controversial. Some studies reported no association of endogenous oestradiol with CVD mortality, but one recent study showed that lower oestradiol levels were associated with increased CVD mortality . With respect to incident CVD, one meta‐analysis showed no conclusive results on the relation between endogenous oestradiol and CVD risk among men .…”
Section: Discussionmentioning
confidence: 99%
“…With respect to incident CVD, one meta‐analysis showed no conclusive results on the relation between endogenous oestradiol and CVD risk among men . In the Framingham Heart Study, low oestradiol levels were associated with an increased risk of atrial fibrillation . Another prospective study showed that high levels of endogenous oestradiol levels predicted incident stroke …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation